Avaliação imaginológica de alterações dentárias e craniofaciais de indivíduos com osteogênese imperfeita: um estudo observacional - Marçal, Felipe Franco (2019)
Osteogenesis imperfecta (OI) is a representative nomenclature of a group of syndromes with collagen type I failure with clinical repercussion in bone fragility, mainly. The oral and craniofacial disorders are not well understood at the level of the distribution in OI types neither modular medical factors. Thus, the present study was composed of two chapters that aim, respectively: 1) to carry out a case-control study on oro-dental findings in OI patients and to analyze medical data as modulators of these findings; 2) to carry out a case-control study on craniofacial cephalometric analysis of OI patients and to analyze medical data influencing these alterations. In Chapter 1, a case-control study was performed with 24 patients diagnosed with OI and 48 controls matched by sex and age. The orofacial findings were evaluated using panoramic radiographs in the TIFF format. In addition, demographic, clinical and related data on bisphosphonate therapy were also tabulated. OI type 4 showed a high prevalence (62.5%) followed by type 1 (37.5%). Regarding clinical severity, the moderate form was the most prevalent (p = 0.028). The imperfect dentinogenesis was observed in 75% of the individuals with OI, and this group showed a high prevalence of dental abnormalities in comparison to the controls. Bisphosphonate therapy was associated with a high prevalence of ectopic teeth (p = 0.007) and dental impaction (p = 0.033). Pulp obliteration was significant in subjects treated with bisphosphonate over a 7-year period (p = 0.026). In chapter 2, twenty-six patients from the SEMENTE (Fortaleza, Ceará) Project with a previous medical diagnosis of OI (GOI) and 52 non-syndromic patients matched by sex and age (GCON) were evaluated for craniofacial characteristics through lateral telerradiography through a cephalometric method for neurocranium, face and teeth alterations. Demographic and medical data were evaluated through medical records and a medical team led by an experienced geneticist. A single examiner performed all patient cephalometric analyzes using the Radiocef Studio 2.0® Software (Kappa Intra-Examiner 0.81). The patients studied with OI (type 1 and 4) generally have neurocranium and reduced faces in sagittal and horizontal dimensions. Type 4 OI in relation to OI type 1 presents a reduced neurocranium in the anterior portion (p = 0.031) and occipital height (p = 0.040), as well as the angle of the base of the deflected skull (p = 0.001). Moreover, reduced facial parameters in this profile of patients with OI type 4, the lower face height (p = 0.045) and posterior superior height (p = 0.012) were identified, as well as the following decreased maxillary data: ANS (p = 0.001) and angle of the palatal plane (p = 0.022). Posterior (p = 0.002) and reduced palatine length (p = 0.048) were more prevalent in patients with OI who used bisphosphonates. In addition, bisphosphonate use period presented moderate inverse correlation with ANB (r = -0537, p = 0.032), and strong direct correlation with Harvold's skeletal difference (r = 0.724, p = 0.002). As conclusions of both studies, it is highlighted that: 1) there is a significant prevalence of dental and craniofacial alterations in patients with OI, and bisphosphonate seems to influence the establishment of these alterations, assuming possible pathophysiological and pharmacokinetic interactions; 2) there were reduced craniofacial changes associated with OI and severely marked in type 4 for maxilla and posterior neurocranium, added to the major maxilo-mandibular alterations in those that use bisphosphonates for a period greater than 10 years.